Possibilities of the use-wear analysis of the lithics from the hunter-gatherer context in Bohemia - Černíková, Monika (Univerzita Pardubice, 2025)
The submitted bachelor's thesis explores the potential of use-wear analysis in understanding the function of lithic tools within a Late Upper Paleolithic hunter-gatherer context in Bohemia. The work is based on a comparison between archaeological artifacts from the Hostim site and a newly created experimental set of flint tools made from glacigenic sedimentary silicite (SGS). These experimental tools were used on a range of materials, including slate, wood, bone, and antlers, to simulate prehistoric activities and generate comparable use-wear traces. The thesis outlines the theoretical background of traceology, describes the experimental process and materials, and offers a microscopic analysis of the wear patterns. Through this comparative approach, the study aims to assess the relevance and limitations of experimental archaeology for interpreting the function of prehistoric tools and offers reflections on methodological consistency. The results indicate both similarities and specific differences between the experimental and archaeological sets.
Možnosti traseologické analýzy štípané industrie u lovecko-sběrač- ských populací v Čechách
Keywords: traceology; experimental archaeology; burin; Upper Paleolithic; lithic industry; Hostim; use-wear analysis; SGS